Fotografia e cor: os esquemas de combinações de cores conduzindo a construção e leitura de fotografias - Egashira, Rafael (2011)
This study aimed to provide a photographic essay experienced by the author of this dissertation and driven by the theory of color. It was assumed that the color photograph is a double construction in the sense that both the photo and color are not neutral. To support this assumption, we introduced elements of the theory of photography that refute the automatic photographic apparatus and brought concepts of color theory that define the color perception as a phenomenon that involves understanding the physical, physiological and cultural features of color. In the chapter on color, we stil present the chromatic harmony, and its main tool, the schemes of color combinations. Such schemes have led to collect a set of photographs which were selected fifteen images to compose this dissertation. Finally, we comment on the presence of color in seven of fifteen photographs takenfor this research.